Mechanisms controlling nucleic acid-sensing Toll-like receptors. (14th February 2018) - Miyake, Kensuke; Shibata, Takuma; Ohto, Umeharu; Shimizu, Toshiyuki; Saitoh, Shin-Ichiroh; Fukui, Ryutaro; Murakami, Yusuke
Abstract: Nucleic acid (NA)-sensing Toll-like receptors (TLRs) respond to DNA/RNA derived from pathogens and dead cells. Structural studies have revealed a variety of molecular mechanisms by which TLRs sense NAs. Double-stranded RNA and single-stranded DNA directly bind to TLR3 and TLR9, respectively, whereas TLR7 and TLR8 bind to nucleosides and oligoribonucleotides derived from RNAs. Activation of ligand-bound TLRs is influenced by the functional status of TLRs. Proteolytic cleavage of NA-sensing TLRs enables ligand-dependent TLR dimerization. Trafficking of ligand-activated TLRs in endosomal and lysosomal compartments is requisite for production of type I interferons. Activation of NA-sensing TLRs is required for the control of viruses such as herpes simplex virus and endogenous retroviruses. On the other hand, excessive activation of NA-sensing TLRs drives disease progression in a variety of inflammatory diseases including systemic lupus erythematosus, heart failure, arthritis and non-alcoholic steatohepatitis. NA-sensing TLRs are targets for therapeutic intervention in these diseases. We here focus on our recent progresses in our understanding of NA-sensing TLRs.